CARBOXYLIC ACIDS OF HERB OF THYMUS CRETACEUS KLOK. ET SCHOST - V. N. Bubenchikova; J. A. Starchak (Фармация и фармакология (Пятигорск), 2015)
We have studied carboxylic acids of the herb of Thymus cretaceus Klok. et Schost which is widespread on a territory of some regions (Belgorod, Voronezh). The study was carried out using gas-liquid chromatography at Agilent Technologies 6890 chromatographer with massspectrometric detector 5973 N. Acids concentration was calculated by means of inner standard.We have established that carboxylic acids of Thymus cretaceus are represented by 34 compounds. Palmitic (1779.02 mg/kg), behenic (1084.15 mg/kg), levulinic (986.24 mg/kg) and linoleic acids (678.82 mg/kg) predominate among fatty acids; citric (9835.14 mg/kg), malonic (447.91 mg/kg) and oxalic acids (388.32 mg/kg) predominate among organic acids; andferulic acid predominate amongphenolcarbonic acids.